A bibliometric analysis of studies on the gut microbiota in cardiovascular disease from 2004 to 2022 - Ming Sheng; Shuquan Xu; Wei-wei Chen; Fa-quan Li; Fa-quan Li; Yi-ming Zhong; Yi-ming Zhong; Yi-xiang Ouyang; Yong-ling Liao; Yong-ling Liao; Ping Lai; Ping Lai (Frontiers in Cellular and Infection Microbiology, 2023)
BackgroundIncreasing evidence indicates that the gut microbiota (GM) is linked to cardiovascular disease (CVD). Many studies on the GM in CVD have been published in the last decade. However, bibliometric analysis in this field is still lacking.MethodsOn 30 September 2022, a search of the Web of Science™ (WoS; Clarivate™, Philadelphia, PA, USA) yielded 1,500 articles and reviews on the GM and CVD. Microsoft Excel and CiteSpace and VOSviewer software were used to analyze publication trends and research hotspots in this field.ResultsOur search generated 1,708 publications on the GM in CVD published between 2004 and 2022, and 1,500 articles and review papers were included in the final analysis. The number of publications relating to the GM in CVD increased from 1 in 2004 to 350 in 2021. China (485 publications, 9,728 non-self-citations, and an H-index of 47) and the USA (418 publications, 24,918 non-self-citations, and an H-index of 82) contributed 32.31%, and 27.85%, respectively, of the total number of publications. Examination of the number of publications (Np) and number of citations, excluding self-citations (Nc), of individual authors showed that Y. L. Tian (Np: 18, Nc: 262, and H-index: 12), from China, is the most productive author, followed by R. Knight (Np: 16, Nc: 3,036, and H-index: 15) and M. Nieuwdorp (Np: 16, Nc: 503, and H-index: 9). The Chinese Academy of Medical Sciences and Peking Union Medical College accounted for the largest number of publications (Np: 62, Nc: 3,727, and H-index: 13, average citation number (ACN): 60.11). The journal Nutrients had the most publications (Np: 73, Nc: 2,036, and ACN: 27.89). The emerging keywords in this field were “monooxygenase 3” (strength 3.24, 2020–2022), “short-chain fatty acid” (strength 4.63, 2021–2022), “fatty liver disease” (strength 3.18, 2021–2022), “metabolic disease” (strength 3.04, 2021–2022), “Mediterranean diet” (strength 2.95, 2021–2022), “prevention” (strength 2.77, 2021–2022), and “intestinal barrier” (strength 2.8, 2021–2022).ConclusionPublications on the GM in CVD rapidly increased in the last decade. The USA was the most influential country in publications in this field, followed by China. The journal with the most publications was Nutrients. Monooxygenase-3, short-chain fatty acids, fatty liver disease, metabolic disease, the Mediterranean diet, intestinal barrier, and prevention are the current hotspots or potential hotspots for future study.